The Origin of the Child Healthcare in the East Coast of Sumatra, 1900s-1940s - Devi Itawan (Universitas Gadjah Mada, 2020)
This article aims to explore the issue of children’s healthcare in the context of colonial expansion on the East Coast of Sumatra. At the early of the 20th century, the birth rate, children, and maternal healthcare have become important issues in discussing health conditions in plantations in East Sumatra. It was a significant shift concerning the realm of East Sumatra plantation health and medical research due to since in the pioneering time, plantation’s medical institutions merely focused on the health of adult male coolies. The phenomenon of high rate of infant mortality in the early 20th century has become a new health problem in the East Coast of Sumatra Plantation. The plantation companies convincing to take further care of the children’s health as it will give a direct effect on plantation hygiene and population growth of the region. In the East Coast of Sumatra, children’s healthcare discourse was a proxy of the colonial capitalism interest, hygiene problems, and needs of population growth.